From “smart growth” to “frontier” intensification: density, YIMBYism, and the development of garden suites in Toronto - Bunce, Susannah (Frontiers in Sustainable Cities, 2023)
Toronto’s official intensification policy has directed increased density primarily through residential development over the last 20 years. Recently, new intensification efforts have focused on increasing density in existing residential neighbourhoods through so-called ‘gentle density’ and ‘missing middle’ built form, as a new ‘frontier’ of intensification. These efforts have included a focus on the production of garden suites on residential properties. In this short intervention, I suggest that Yes-In-My-Backyard narratives, which celebrate intensification, raise problematic arguments under the guise of sustainable urbanism and liberal progressive politics that foreclose important critiques of intensification. I argue that increased YIMBYism and new intensification efforts in Toronto are entwined with homeownership wealth-building and market-oriented property development.